Flujo y herramientas de trabajo de los documentalistas en laSexta Noticias - Martín López, Carlos (Cuadernos de Documentación Multimedia, 2009)
The author assesses news and documentation-flows in the daily labour of an editorial team in a Spanish national channel news department, called LaSexta Noticias, where the use of videotapes has completely disappeared in the production line, being replaced with digital technology. The new production environment is bases in MAM (Media Asset Management), which has changed workflows in TV production and, obviously, the tools used by information. After a deep analysis of the new dynamics, the author concludes that the role of media librarians is getting closer and closer to journalist’s one, sharing both departments the same software and procedures in the edition of images, so much so that sometimes both take part in the same level of the production line.
Keywords: Television; Audiovisual Documentation; Digitization; MAM; Media Asset Management; Documentalist; Digital Archives; Professional profiles